Inclusão digital para a redução de desigualdades sociais: a apropriação e o uso das tecnologias da informação para a atuação cidadã - Heloisa Helena Fernandes Soares de Albuquerque (2005)
This work evaluates the development of the Cidadão.NET (Citizen.NET) Digital Inclusion Program sponsored by the Government of the Minas Gerais State in Brazil, through its Special Secretariat for the North of Minas and the Jequitinhonha and Mucuri River Valleys Development (SEDVAN, in Portuguese) and its Institute for the Development of the North and Northeast Regions of Minas Gerais (IDENE). We aimed at analysing the potential of the Program to effectively create social and digital inclusion opportunities to its users. Our evaluation was based on social and information sciences studies of the connection between subject and citizenship, and of the essential role of information processes in modern society. Our conclusions are based on a quantitative-descriptive field work carried out at the cities of Brasília de Minas, Novo Oriente de Minas, Janaúba, Montes Claros and Minas Novas, which were selected among the 36 cities first equipped with a Cidadão.NET Telecentre in the State. Research tools were semi-open questionnaires answered by telecentre users, semistructured interviews with the instructors, and open interviews with local managers and withEducational and General Coordinators. Our results indicate that theCidadão.NET Program presents an excellent potential for thepromotion of digital inclusion opportunities. These can also contribute to users social inclusion if the Program is structurally re-configured. Users local context and social and financial conditions are to be considered in the re-evaluation and improvement of the Program, as well as in the development of the teaching and learning activities. Users also needto be properly prepared to a critical analysis of the digital environment and information, and a substantial investment is needed to make this preparation possible. Additionally, it is urgent the implementation of a Program management model to facilitate the attainment of its originaland new purposes. Finally, digital inclusion indicators are to be established for the monitoring and continuous evaluation of the Cidadão.NET Program.